2021
DOI: 10.1016/j.envres.2020.110420
|View full text |Cite
|
Sign up to set email alerts
|

Does greenery experienced indoors and outdoors provide an escape and support mental health during the COVID-19 quarantine?

Abstract: Background The COVID-19 pandemic has profoundly changed people's ability to recreate in public green spaces, which is likely to exacerbate the psychological impacts of the pandemic. In the current study, we seek to understand whether greenery can support mental health even with insufficient outdoor exposure in times of physical isolation from the outdoor environment. Methods Between 17 May and 10 June, 2020, we conducted an online survey among 323 students (21.99 ± 3.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
161
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(182 citation statements)
references
References 116 publications
(142 reference statements)
16
161
3
2
Order By: Relevance
“…Our study is largely in agreement with the findings from the previous studies. For example, two recent publications -from Japan and Bulgaria -have reported that increased frequency of green area use and/or increased access to green views through the windows at home during the Covid-19 pandemic-related restrictions were associated with positive mental health effects (2,10). In the present study, we did not investigate the effect of the green window views; however, we believe that using (among others) the rather small buffer sizes (such as 50m surrounding the place of residence) did reflect the relative difference in the quantity of greenness that people were able to see through their windows.…”
Section: Discussionsupporting
(Expert classified)
See 3 more Smart Citations
“…Our study is largely in agreement with the findings from the previous studies. For example, two recent publications -from Japan and Bulgaria -have reported that increased frequency of green area use and/or increased access to green views through the windows at home during the Covid-19 pandemic-related restrictions were associated with positive mental health effects (2,10). In the present study, we did not investigate the effect of the green window views; however, we believe that using (among others) the rather small buffer sizes (such as 50m surrounding the place of residence) did reflect the relative difference in the quantity of greenness that people were able to see through their windows.…”
Section: Discussionsupporting
(Expert classified)
“…During the time of increased uncertainty, nature around our homes may play a key role in mitigating against adverse mental health outcomes (2,10). A myriad of scientific studies have suggested that experiencing greenness and nature is associated with mental health benefits (11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This everyday contact with nearby nature—either through a window view at the home 35 , 54 , 66 or on the street 18 , 51 —has been shown to be beneficial for mental health and wellbeing. During the COVID-19 pandemic when people were encouraged to stay-at-home, those who had views of trees and greenspace from the home reported lower rates of depression and anxiety 67 . These studies suggest that ‘unintentional’ 17 contact with nearby nature in daily life is important for mental health.…”
Section: Discussionmentioning
confidence: 99%